Theta Burst Transcranial Magnetic Stimulation of Fronto-Parietal Networks: Modulation by Mental State. Issue 3 (2020) - Taylor, Stephan F.; Lee, Taraz G.; Jonides, John; Tso, Ivy F.; Hernandez-Garcia, Luis
No abstract available